PSIV-38 Conjoint analysis of transcriptome and microRNA of mammary epithelial cells of Chinese holstein cow. (7th December 2018) - Xia, L; Zhao, Z; Fang, X; Lu, C; Yang, R
Abstract: Mlik is an essential nutrient in people's life, the quantity and quality of milk production in bovine is well known to be correlated with differential gene expression in mammary tissue. To better understand the milk fat and milk protein synthesis and metabolic metabolism at the molecular level, we performed a conjoint analysis of transcriptome and microRNA data of mammary epithelial cells of lactating cow with high milk fat percentage and low milk fat percentage. 10 most upregulated genes (C4BPA, IGCGAMMA, BOLA, IGLL1, etc.) and ten most downregulated genes (PRSS2, ATF3, NT5E, etc.) between high milk fat percentage group and low milk fat percentage group were selected for qPCR confirmation validation. Furthermore, we verified the targeted relationship between the differentially expressed genes (KLF6 and NDRG2) and the differentially expressed microRNA (Bta-MiR-2382-5p) by qPCR and the dual luciferase reporter system. The results showed that 190 DEGs were regulated by 30 microRNA. Correlation analysis found that DEGs significantly enriched in 488 GO terms including response to glucocorticoid and very-low-density lipoprotein particle receptor activity. KEGG analysis showed that DEGs were mainly distributed among 12 pathways including tyrosine metabolism. The dual luciferase reporter system data show luciferase activity was significantly lower in cells that miR-2382-5p cotransfected with KLF6 and NDRG2 gene reporter vectors (pmiR-KLF6-WT, pmiR-NDRG2-WT) than in cells cotransfected with pmiR-KLF6-MUT and pmiR- NDRG2-MUT. It is proved that miR-2382-5p target sites existed in 3'UTR of KLF6 and NDRG2. The expressions of miR-2382-5p were negatively correlated with levels of mRNA of KLF6 and NDRG2 gene, suggesting that miR-2382-5p might play an important role in regulation of KLF6 and NDRG2 gene expression. Our results identified novel candidate DEGs and microRNA correlated with milk fat percentage traits, which will be valuable for molecular mechanism studies of lipometabolism in dairy cows.